Evaluation of Clinical Pathway Implementation for Acute Appendicitis at Mitra Medika General Hospital, Medan Tanjung Mulia, 2022 - Liem, John Barker; Siregar, Rabia Ulfa (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2025)
This study evaluated the implementation of the Clinical Pathway for acute appendicitis at Mitra Medika General Hospital, Medan Tanjung Mulia, in 2022. The objective was to assess the compliance level of healthcare professionals with the established clinical pathway and to identify factors influencing its application in patient management. A descriptive retrospective design was employed, using medical records of acute appendicitis patients treated during the specified period. Data analysis focused on adherence to diagnostic, therapeutic, and postoperative care standards outlined in the clinical pathway. The results showed that overall compliance was high, particularly in preoperative and operative phases, while postoperative follow-up displayed moderate adherence due to variations in discharge planning and documentation. Factors affecting implementation included staff workload, availability of medical resources, and differences in clinical judgment. It was concluded that the clinical pathway was effectively implemented, although improvements are required to enhance consistency in postoperative care. Strengthening monitoring systems and conducting regular training are recommended to improve adherence and optimize patient outcomes.